Pengembangan Media Pembelajaran Boardgame Matematika Kelas XI Dengan Materi Matriks Di SMA Negeri 105 Jakarta - Desy Henika Putri Butar-Butar; Ilmi Arifiyah; Mella Novallina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Board games are one of the learning media to increase student interest in a subject. And on this occasion I made